LITERATURE REVIEW OF FLYING FISH: BIOLOGY, DISTRIBUTION, FLYING FISH FISHERIES, AND CURRENT RESEARCH: Tinjauan Pustaka Ikan Terbang: Biologi, Distribusi, Perikanan Ikan Terbang, dan Penelitian Terkini - Putri, Rini Sahni; Jaya, Indra; Pujiyati, Sri; Agus, Syamsul Bahri; Palo, Mahfud (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
This article presents various literature related to flying fish from 1930 to the present, which are shown in the form of aspects of biology, distribution, fisheries, and utilization of Current Technology in Flying Fish Research. This study was conducted through a systematic search and review of various articles, books, dissertations, and theses that discuss flying fish. Literature studies related to flying fish are important to provide more complete information required to maintain the sustainability of their resources. This study shows the classification, type, spawning process, body shape, ability to glide in the waters, distribution, fishing technology, and current technology in various researches. Keywords: biology, distribution, flying fish, fisheries